Stanford Type A Acute Aortic Dissection with Intimal Intussusception - Yanase, Yohsuke (Ann Thorac Cardiovasc Surg, 2018)
In case of complete circumferential dissection of the ascending aorta, the dissected flap has the potential to fold backwards, causing several complications. We report two cases of Stanford type A acute aortic dissection (AAD) whose intimal flaps intussuscepted into the left ventricular outflow tract. Case 1: A 41-year-old man with AAD in whom transthoracic echocardiography (TTE) showed the dissected flap as folded back into the left ventricular outflow tract, causing severe aortic regurgitation (AR) with rapidly progressing acute pulmonary edema. Despite performing salvage surgery, the patient could not be rescued. Case 2: An 81-year-old man with annuloaortic ectasia developed Stanford type A AAD. TTE showed an extremely mobile intimal flap intussuscepting into the left ventricular outflow tract. However, AR was not severe as it was prevented by the flap itself. The patient was rescued by performance of the modified Bentall procedure.